The Use of Mobile Learning Technologies for an Online Mathematics Course: Student Opinions in The Pandemic Process - Tezer, Murat; Gülyaz, Meryem (International Journal of Interactive Mobile Technologies (iJIM), 2022)
This study aims to examine the opinions of university students about using mobile learning Technologies in an online mathematics course during the pandemic (COVID-19) period. The participant group of the study consists of 266 university students studying at a private university. In the study, a mixed research method, in which quantitative and qualitative research methods are used, was used. A questionnaire form which was "Student Opinions Regarding Using Mobile Learning Technologies in an Online Mathematics Lesson During the Pandemic Process" created by the researchers and open-ended questions were used to reveal the opinions of the students about the online mathematics lesson. According to the results of the study, one can be seen that the majority of the students make an effort and spare time to understand mathematics in online lessons who use mobile learning technologies during the Covid-19 pandemic process. In addition, they argued that the majority of the students believe that they will be successful in the exam at the end of the online mathematics lesson by using mobile learning technologies and that it is easy to follow the mathematics lesson online using mobile learning technologies during the Covid-19 pandemic process, depending on the teacher giving the lesson. In addition, they stated the inadequacy of knowledge in the field of numeracy and the lack of technical infrastructure in distance education among the difficulties experienced by the students in the online mathematics course. As learning strategies in the virtual environment, the students stated that they did it again and again, watched the live lesson videos over and over, prepared an individual study program for themselves, took notes, attended regular classes, and watched educational videos by using mobile learning technologies.